Solubility modeling of Sabah green Robusta coffee (coffea canephora) bean oil extracted using supercritical carbon dioxide - Sarah Aisyah Khurun Hizar; Hasmadi Mamat; Wolyna Pindi; Norliza Julmohammad; Siti Faridah Mohd Amin; Mohd Azrie Awang; Jumardi Roslan; Muhammad Abbas Ahmad Zaini; Nicky Rahmana Putra; Abdul Aziz Jaziri; Norzalizan Ishak; Ahmad Hazim Abdul Aziz (MDPI, 2025)
This study investigates the solubility correlation of oil extracted from Sabah green Robusta coffee (Coffea canephora) beans through supercritical carbon dioxide (SC-CO2) extraction. Sabah, recognized as the largest coffee-producing region in Malaysia, serves as a significant source of Robusta beans for this research. The solubility of coffee bean oil was evaluated under varying pressures (10–30 MPa) and temperatures (40–80 °C). The maximum solubility, 2.681 mg/g CO2, was recorded at 30 MPa and 40 °C, whereas the lowest solubility, approximately 0.440 mg/g CO2, occurred at 20 MPa and 80 °C. A clear inverse relationship between solubility and temperature was observed, with solubility decreasing as temperature increased to 80 °C. Conversely, elevated pressure, particularly at 30 MPa, enhanced solubility due to the increased density and solvent power of SC-CO2. Experimental data exhibited strong agreement with Chrastil’s equation, yielding a relatively low percentage error of 3.37%, compared with 14.57% for the del Valle-Aguilera model. These findings demonstrate the reliability of Chrastil’s model in predicting the solubility of Sabah green coffee bean oil in SC-CO2. Overall, the research highlights the potential of SC-CO2 extraction as a sustainable, solvent-free approach for obtaining high-quality coffee oil extracts, with promising applications in the food industry and possible extension to the recovery of other bioactive compounds in food processing.